Evaluation of the CMIP6 models in simulating climatic variables in the Cantareira Water Production System - Oliveira, Lucas Rickli de; Destro, Cesar Augusto Medeiros; Lucas, Murilo Cesar (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The Cantareira Water Production System is highly susceptible to the effects of climate changes. Extreme drought events affect reservoir levels and the water supply of millions of people. Therefore, water resource managers need reliable information about the of these events. Understanding the ability of global climate models to simulate climatic variables is essential to obtain reliable forecasts. In this context, this work evaluates the performance of 10 models from the recent Coupled Model Intercomparison Project Phase 6 (CMIP6) in simulating the main climatic variables for the Cantareira System area. For this, several statistical metrics (r, RMSE, Pbias and KGE) were used to evaluate the performance of each model in relation to the observed period (2000-2013) and combine the results to rank the top performances. The results show that the best ranked models were EC-EARTH3, INM-CM4_8, INM-CM5, ACCESS-ESM1-5 and MRI-ESM2, depending on the climate variable. Overall, the study highlights the importance of individual evaluation of MCGs and their appropriate selection to generate reliable information in climate studies.
Keywords: CMIP6; Global Climate Models; Climate Change